Example 3: Find the quadratic equation if we know that the roots are 2 and 3.
It is easy to find the solutions of the x from the square equation by the following steps.

(1) 
Now we can add and multiply the solutions to get the solutions as a function of the coefficients of the square equation.

(2)
(3) 
Substitute given solutions into equations (2) and (3).
b = −(x_{1} + x_{2})a = −(2 + 3)a = −5a
c = x_{1}x_{2}a = 2 ‧ 3a = 6a
If we chose a to be equal to 1 than the quadratic equation will be: x^{2} − 5x + 6 = 0
